Beyond dichotomies: Gender and intersecting inequalities in climate change studies - Djoudi, H.; Locatelli, Bruno; Vaast, C.; Asher, K.; Brockhaus, Maria; Sijapati Basnett, Bimbika (Springer, 2016)
Climate change and related adaptation strategies have gender-differentiated impacts. This paper reviews how gender is framed in 41 papers on climate change adaptation through an intersectionality lens. The main findings show that while intersectional analysis has demonstrated many advantages for a comprehensive study of gender, it has not yet entered the field of climate change and gender. In climate change studies, gender is mostly handled in a men-versus-women dichotomy and little or no attention has been paid to power and social and political relations. These gaps which are echoed in other domains of development and gender research depict a ‘feminization of vulnerability’ and reinforce a ‘victimization’ discourse within climate change studies. We argue that a critical intersectional assessment would contribute to unveil agency and emancipatory pathways in the adaptation process by providing a better understanding of how the differential impacts of climate change shape, and are shaped by, the complex power dynamics of existing social and political relations.